Suunnitelmatalous Neuvosto-Karjalassa 1928-1941 : paikallistason rooli Neuvostoliiton teollistamisessa - Autio, Sari (Suomalaisen Kirjallisuuden Seura, 2002)
Summary: Planned economy in Soviet Karelia 1928-1941. The role of the local level in the industrialisation of the Soviet Union.